What determines the quality of remuneration policy in financial holding companies? An analysis based on the example of the UniCredit Group - Agata Wieczorek; Agata Szymańska (Journal of Banking and Financial Economics (JBFE), 2022)
This study seeks to examine the quality of the remuneration policy (RP) and identify its main determinants within a financial holding company (FHC) - the UniCredit Group. The results show that the quality of remuneration policy in the examined FHC was low. Although the dominant bank is characterized by high remuneration policy standards, the rest of the group is not. The empirical approaches used show that remuneration policy quality was positively related to the size of the bank and the transparency index of the remuneration policy, but negatively affected by the selected corporate governance determinants.
Keywords: G2; G34; G38; 330; banking and insurance; corporate governance; financial holding company; remunerationpolicy; quality index of the remuneration policy